Aruba: uma arquitetura para geração de serviços a partir de sistemas legados de forma não intrusiva - Larentis, Andrêsa Vargas (Universidade do Vale do Rio do Sinos, 2008)
The traditional software development is based on a model focused in answering a set of business requirements (generally an object or component model), but it needs to be prepared to deliver solutions to business needs that may occur during the process. This way, a service based model may represent a new technology approach to meet these needs. At the Brazilian and international scenario there are many legacy systems. These systems are being currently in use and often are built on old technologies that do not allow much reuse. Porting these systems to a service based technology, aiming large scale reuse, needs analysis of the existing code and some customizations to make services available without compromising its functions. This work explains an architecture called Aruba that allows service generation from legacy systems with no need of legacy code change. This solution uses the Web Services technology, which allows service description and use through WSDL and SOAP (all XML based), and uses a database as re
Keywords: decomposição; geração de serviços; integração; sistemas legados; aplicações; application decomposition; application integration; web services; Ciências Exatas e da Terra